2019
DOI: 10.1525/collabra.203
|View full text |Cite
|
Sign up to set email alerts
|

Near and Far Transfer in Cognitive Training: A Second-Order Meta-Analysis

Abstract: Theory building in science requires replication and integration of findings regarding a particular research question. Second-order meta-analysis (i.e., a meta-analysis of meta-analyses) offers a powerful tool for achieving this aim, and we use this technique to illuminate the controversial field of cognitive training. Recent replication attempts and large meta-analytic investigations have shown that the benefits of cognitive-training programs hardly go beyond the trained task and similar tasks. However, it is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 83 publications
10
123
0
5
Order By: Relevance
“…These research designs do not control for the possibility of placebo effects. Intervention studies must include an active control group to control for possible placebo effects [39], thus it will be necessary to compare the effect of board game groups and active control groups in future research. Third, in the articles selected for the present review, some studies were conducted with relatively small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…These research designs do not control for the possibility of placebo effects. Intervention studies must include an active control group to control for possible placebo effects [39], thus it will be necessary to compare the effect of board game groups and active control groups in future research. Third, in the articles selected for the present review, some studies were conducted with relatively small sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, WM training does not enhance children's domain-general cognitive skills or academic achievement (Aksayli, Sala, & Gobet, 2019;Melby-Lervåg et al, 2016;Sala & Gobet, 2020). The same applies to action and nonaction videogame training and brain training (Duyck & Op de Beeck, 2019;Kassai, Futo, Demetrovics, & Takacs, 2019;Libertus et al, 2017;Lintern & Boot, 2019;Sala et al, 2019a;Sala, Tatlidil, & Gobet, 2018, 2019bSimons et al, 2016).…”
Section: Beyond Meta-analytic Evidencementioning
confidence: 99%
“…Analogously, H0 was substantially supported only if BF < 0.333 (i.e., H0 three times more likely to be true than H1). Since the priors were conditional to the type of controls employed by the primary study (as indicated by Sala et al, 2019a), these analyses were carried out after running moderator analysis. The analyses were carried out with the bayesmeta R package (Röver, 2017).…”
Section: Bayesian Analysismentioning
confidence: 99%
“…On the other hand, previous research also indicated that the effects of computer-based training could transfer to an untrained domain (Goldin et al, 2014;Liu et al, 2015). In fact, most cognitive training programs are designed to improve not only the specified domain but also the general cognitive ability or, at least, some core cognitive mechanisms (Sala et al, 2019a). Therefore, it is vital to examine whether computer-based training is effective for far-transfer effects.…”
Section: Introductionmentioning
confidence: 99%